2006
DOI: 10.1200/jco.2005.04.8207
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Pain in Advanced Stage Prostate Cancer: Results of a Southwest Oncology Group Randomized Trial Comparing Docetaxel and Estramustine to Mitoxantrone and Prednisone

Abstract: DE had superior clinical efficacy (overall survival, time-to-progression, and prostate-specific antigen declines) with similar global QOL and pain palliation in the MP arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…In SWOG 99-16, palliation of bone pain and global quality of life were not significantly different between the 2 treatment arms. 34 In contrast, pain response rates in the docetaxel group were 35% and 31% for every-3-week and weekly docetaxel, respectively, significantly better than the 22% observed with mitoxantrone. Both pain response and PSA declines correlated with survival in patients treated on the TAX327 study.…”
Section: Single-agent Docetaxel Therapymentioning
confidence: 68%
“…In SWOG 99-16, palliation of bone pain and global quality of life were not significantly different between the 2 treatment arms. 34 In contrast, pain response rates in the docetaxel group were 35% and 31% for every-3-week and weekly docetaxel, respectively, significantly better than the 22% observed with mitoxantrone. Both pain response and PSA declines correlated with survival in patients treated on the TAX327 study.…”
Section: Single-agent Docetaxel Therapymentioning
confidence: 68%
“…Other clinically important endpoints were redefined, like the evaluation of pain intensity and other parameters, such as the use of analgesic drugs, the performance status and quality of life [15] . Several studies conducted in patients with mCRPC symptoms have demonstrated that mitoxantrone or docetaxel in combination with corticosteroids could improve symptoms but they were not able to significantly increase the survival benefit [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, systemic cytotoxic therapies have demonstrated improvements in pain and quality of life among patients with advanced cancers in many trials [3,50,63]. In a recent clinical trial in patients with advanced prostate cancer (N=674), mitoxantrone plus prednisone or docetaxel plus estramustine both palliated pain to a similar extent (24% and 21% of patients in each group, respectively) [9]. In another study, in patients with advanced solid tumors (N=146), chemotherapy produced pain relief compared with baseline based on questions from the EORTC QLQ-C30 [5].…”
Section: Bone Painmentioning
confidence: 94%